Interaction effects of region-level GDP per capita and age on labour market transition rates in Italy - Luca Zanin; Raffaella Calabrese (IZA Journal of Labor Economics, 2017)
The aim of this paper is to measure the effect of the interaction between age for the population of males and females aged 18 to 74 and region-level GDP per capita on labour market transition probabilities in Italy. We compare different occupational states in a sample of males and females who remained in their region of residence at two points in time (12 months apart). We estimate the transition probabilities using a flexible hierarchical logit model with interaction effects between worker age and region-level GDP per capita. We apply this model using longitudinal data from the Italian Labour Force Survey that cover the 2004-2013 period. We find empirical support for the assumption that people in the same age cohort have different labour market opportunities based on the level of GDP per capita in their region of residence. These differences are particularly relevant among younger workers.
Keywords: C14; J01; J21; J68; 330; Transition probabilities; Flexible hierarchical logit model; Tensor interaction product; Markov chain framework; Labour market policies